Two new species of Amphinemura (Plecoptera: Nemouridae) from Yunnan Province, southwestern China - Li, Mengyu; Yang, Ding; Li, Weihai (Zootaxa, 2023)
Two new species of nemourid stonefly, Amphinemura kondratieffi sp. nov. and A. setosa sp. nov., are described from Yunnan Province of southwestern China. The relationships between the new species and their related species within the genus or species group are discussed.